Targeting gut microbiota in osteoporosis: impact of the microbial-based functional food ingredients - Pauline Duffuler; Khushwant S. Bhullar; Jianping Wu (Food Science and Human Wellness)
Osteoporosis is the most common bone disorder, characterized by low bone mineral density and microarchitectural deterioration of the bone tissue, which increases the susceptibility to fracture. In the past decade, emerging research findings reported the implication of gut microbiota on bone health and osteoporosis pathology. Osteoporotic patients or individuals with a lower bone mineral density exhibit an alteration of the gut microbiota at several taxonomic levels. Additional reports demonstrate that gut microbiota regulates bone metabolism through the modulation of the gut function (mineral availability and absorption, gut integrity), the immune system, and the endocrine system. Thus, based on the vital role of gut microbiota on bone health, it has emerged as a novel therapeutic target for the prevention of bone loss and the treatment of osteoporosis. Microbial-based functional food ingredients, such as probiotics, prebiotics, synbiotics, and fermented foods, have been developed to alter the gut microbiota composition and function and thus, to provide benefits to the host bone health. Despite promising initial results, microbial-based therapies are still under investigation. Moreover, additional animal studies and clinical trials are needed to understand the interactions between gut microbiota and bone metabolism before further applications.